Linear And Nonlinear Dynamic Modelling Of Motorized Prosthetic Hand System - Rozaimi , Ghazali (Asian Research Publishing Network (ARPN), 2016)
This paper described the dynamic modeling of motorized prosthetic finger system.Recently prosthetic hands become more importance because its capability to become potential substitute hand for amputee.By using various type of actuators,prosthetic hands become more practical as it could operate with neuro motors energy which initiated by the Automatic Nervous System (ANS) of the brain.However the mathematical modeling of the system needs to be appropriately determined to ensure the accuracy of the control design later on.This paper explained the linear and nonlinear dynamic modeling of the system using Lagrangian equation.The model of the system is derived by considering the energies of the finger when it is actuated by the DC motor.The linear and nonlinear model based on the Lagrangian function of the motion of the finger is evaluated based on the characteristic of the output response.The results show the significant finding of the output characteristic of the linear and nonlinear dynamic modeling of the system.